2022
DOI: 10.1088/1748-9326/ac8c58
|View full text |Cite
|
Sign up to set email alerts
|

Exposure of agricultural workers in California to wildfire smoke under past and future climate conditions

Abstract: Wildfire activity in the western U.S. has increased in frequency and severity in recent decades. Wildfire smoke emissions contribute to elevated fine particulate matter (PM2.5) concentrations that are dangerous to public health. Due to the outdoor and physically demanding nature of their work, agricultural workers are particularly vulnerable to wildfire smoke pollution. In this study, we quantify the potential exposure of agricultural workers in California to past (2004–2009) and future (2046–2051) smoke PM2.5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 41 publications
0
17
0
1
Order By: Relevance
“…Our conclusion that more western wildfire-specific monitoring is needed to capture population exposure to wildfire smoke is in agreement with the findings of two studies published in 2022, which used very different methodologies�one used mode decomposition on the Di estimates 45 and the other used chemical transport modeling under past and future climate conditions. 46 Both of these studies focused on the network of EPA monitors (and our study additionally used the USFS mobile smoke monitors), but another possibility for future years is including data from low-cost air quality sensors, which are much less accurate than EPA monitors and the mobile smoke monitors, but can provide more high-resolution spatial and temporal information on PM 2.5 . 11 During the 2021 fire season, the USFS deployed low-cost sensors to fill a shortage in the smoke monitors.…”
Section: Environmental Science and Technology Pubsacsorg/est Articlementioning
confidence: 99%
“…Our conclusion that more western wildfire-specific monitoring is needed to capture population exposure to wildfire smoke is in agreement with the findings of two studies published in 2022, which used very different methodologies�one used mode decomposition on the Di estimates 45 and the other used chemical transport modeling under past and future climate conditions. 46 Both of these studies focused on the network of EPA monitors (and our study additionally used the USFS mobile smoke monitors), but another possibility for future years is including data from low-cost air quality sensors, which are much less accurate than EPA monitors and the mobile smoke monitors, but can provide more high-resolution spatial and temporal information on PM 2.5 . 11 During the 2021 fire season, the USFS deployed low-cost sensors to fill a shortage in the smoke monitors.…”
Section: Environmental Science and Technology Pubsacsorg/est Articlementioning
confidence: 99%
“…Farmworkers represent another key occupational group disproportionately exposed not only to wildfire smoke [68] but also to COVID-19 [69]. A study of California farmworkers found that COVID-19 infections were elevated by a factor of four due to essential worker status and socioeconomic vulnerabilities [69].…”
Section: Limitations Of Included Studiesmentioning
confidence: 99%
“…Such progress in spatial resolution has led to an increased focus on urban centers at the expense of rural communities also vulnerable to pollution, especially from smoke (Pellow, 2016). For example, outside of metropolitan hubs, the Central Valley in California and Central/Eastern Washington State have large populations of non‐white Hispanic agricultural workers who are disproportionately affected by smoke PM 2.5 as an occupational hazard (Cedar River Group, 2012; Chandrasekaran, 2021; Garcia, 2007; Marlier et al., 2022), but whose PM 2.5 exposure is not well monitored (deSouza and Kinney, 2021; Kelp et al., 2022). The Navajo nation, a Native American reservation in the Southwest, is the largest land area held by an indigenous tribe in the United States (Guiterman et al., 2019).…”
Section: Introductionmentioning
confidence: 99%